Assessing the Teaching Quality of Economics Programme: Instructor Course Evaluations - Eglantina Hysa; Naqeeb Ur Rehman (National Research Mordova State University, 2019)
Introduction.In recent years, measuring the efficiency and effectiveness of higher education has become a major issue. Most developed countries are using national surveys to measure teaching and assessment as key determinants of students' approaches to learning which have direct effect on the quality of their learning outcomes. In less developed countries, there does not exist a national survey. This paper aims to propose an original questionnaire assessing the teaching quality. The specifics of this questionnaire, termed as the Instructor Course Evaluation Survey, is that it addresses three main dimensions, such as: Learning Resources, Teaching Effectiveness, and Student Support. Materials and Methods. The paper opted for an analytic study using 3,776 completed questionnaires. This is a case study applied to the students enrolled in economics program in a private university in Albania. The Instructor Course Evaluation Survey design was supported by the literature review, identifying the three main dimensions included in the questionnaire. The reliability was tested with Cronbach's alpha and with Confirmatory Factor Analysis. The use of Confirmatory Factor Analysis helps in identifying issues of multi-dimensionality in scales. Results. The paper provides empirical insights into the assessing methodology and brings a new model of it. The finding suggests that Learning Resources, Teaching Effectiveness and Student Support increase the quality of teaching. Because of the chosen research target group, students from economics program, the research results may not be generalizable. Therefore, researchers are encouraged to test the proposed statements further. Discussion and Conclussion.The paper includes implications for the development of a simple and useful questionnaire assessing the quality of teaching. Although Instructor Course Evaluation Survey was applied specifically to economics program, the proposed questionnaire can be broadly applied. This paper fulfills an identified need to propose an original and simple questionnaire to be used from different universities and programs to measure the quality of teaching.